An Integrated, Clinician-focused Telehealth Monitoring System to Reduce Hospitalization Rates for Home Health Care Patients with Diabetes - José A. Pagán PhD; Hsueh-Fen Chen PhD; M.Christine Kalish MBA, CMPE (SAGE Publishing, 2011)
Diabetes is one of the leading causes of death and disability in the United States, and hospitalization rates related to this health condition are high and costly to the United States health care system. The purpose of this study was to examine the effect of an integrated, clinician-focused telehealth monitoring system on the probability of hospitalization for home health care patients with diabetes. The study included 2009 data from 699 Medicare beneficiaries receiving home health services in Texas and Louisiana. Propensity score matching, logistic regression, and post-estimation parameter simulation were used to assess how telehealth affects the probability of hospitalization during the first 30 days of home health care. The 30-day hospitalization probability for telehealth and non-telehealth patients was 7% and 19%, respectively. Patients in the telehealth group had a 12 (95% confidence interval = 4.2-20.3) percentage point-lower probability of hospitalization within the first 30 days of home health care than non-telehealth matched patients. The results suggest that telehealth monitoring systems that integrate skilled clinicians with critical care experience can lead to substantially lower hospitalization rates during the first 30 days of home health care, large cost savings, and more effective home health management of patients with diabetes.